Engineered bacteriophage lysins as novel anti-infectives - Yang, Hang; Yu, Junping; Wei, Hongping (Frontiers in Microbiology, 2014)
Bacteriophage lysins, the highly evolved special peptidoglycan hydrolases, have long been demonstrated to be an effective enzybiotics in various infectious models. The modular structure of lysins makes it possible to design bioengineered lysins that have desired properties, such as higher activity, broader killing spectrum. Moreover, lysins can even be engineered to kill gram-negative bacterial pathogens from without, a property that is unavailable for natural lysins. In this era of ever increased multidrug resistant pathogens, engineered lysins represent a new class of enzybiotics that are powerful and readily available to fight the antimicrobial resistance.